Intelligence, empathy, and memory: Exploring moral enhancement through gene editing, training, and computer–brain interfaces - Braden Molhoek (HTS Teologiese Studies/Theological Studies, 2021)
In this research article, I seek to expand the conversation regarding moral enhancement by identifying traits or capacities that if enhanced would lead to an increase in moral behaviour. I decided to focus on the three capacities: intelligence, empathy and memory. These abilities do not necessarily lead to moral behaviour on their own; however, building on a study on the relationship of intelligence and morality, I argued that enhancing intelligence and empathy simultaneously allows for moral behaviour as an emergent property. Intelligence alone is not sufficient because even though greater intelligence leads to more prosocial behaviour, prosocial behaviour is not inherently moral. Empathy alone can lead to partiality, especially favouring those who are a part of one’s in-group. The virtue of prudence, practical wisdom, relies on more than intellect or reason; it requires lived experience in order to effectively deliberate. Memory provides intelligence with that information. There are a variety of ways in which human enhancement can be pursued. I chose to focus on three methods in this study: gene editing, training and computer–brain interfaces. Turning to the existing scientific literature, I attempted to find examples or potential ways in which intelligence, empathy and memory could be enhanced through these methods. Genetic examples are difficult given the complexity of multi-gene traits, and that heritability is only a small percentage of overall variance. Training these capacities has had limited success, and there is no consensus in the literature on how effective is the training. Computer–brain interfaces appear to offer potential, but some experiments have only just begun on human subjects, whilst other approaches are still being tested on other animals.